Improving Employee Performance Through Work-Life Balance and Job Motivation at Pdam Majalengka - Dewi Rosmayanti Khoirunnisa; Noveria Susijawati (Green Publisher Indonesia, 2026)
This study aims to analyze efforts to improve employee performance (Y) at PDAM Majalengka through the enhancement of work-life balance (X1) and work motivation (X2). The research applies a quantitative method with an associative approach and a cross-sectional design. Data were collected through structured questionnaires distributed to 111 employees who met the predetermined research criteria. The sampling technique applied purposive sampling to ensure respondents possessed relevant job experience and organizational tenure. Data analysis procedures consisted of validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing using the t-test supported by IBM SPSS version 26. The findings indicate that work-life balance exerts a positive and statistically significant effect on employee performance (sig. 0.030 < 0.05). Work motivation demonstrates a positive and statistically significant effect on employee performance (sig. 0.025 < 0.05). The regression model confirms that both independent variables contribute meaningfully to variations in performance levels among employees. The Adjusted R Square value of 0.115 indicates that 10% of the variance in employee performance is explained by work-life balance and work motivation. The remaining 90% of performance variance reflects the influence of other variables beyond the scope of the present research model, including organizational culture, leadership style, job satisfaction, compensation systems, and work environment factors.